Bunching with the Stars: How Firms Respond to Environmental Certification - Houde, Sébastien (Management Science, 2022)
Voluntary environmental certification programs have been a popular tool used by governments, industry groups, and nonprofit organizations alike. A central question in the design of such programs is who should pay for them. In a context where firms respond strategically to a certification, the answer to this question is a priori ambiguous and, ultimately, empirical. This paper provides important insights on this question using ENERGY STAR, a voluntary certification program for energy-efficient products, as a case study. I show that firms are highly strategic with respect to this certification and extract consumer surplus associated with certified products via three mechanisms. They offer products that bunch at the certification requirement, differentiate certified products in the energy and nonenergy dimensions, and charge a price premium on certified products. I use these findings to motivate a structural econometric model with firms’ strategic behaviors with respect to product line and pricing decisions and to investigate the incidence of a certification licensing fee to fund the certification program. This paper was accepted by Juanjuan Zhang, marketing.